Successful short interval staged surgery in synchronous type A aortic dissection and giant abdominal aortic aneurysm patient. Issue 10 (October 2022) - Hu, Zhipeng; Wang, Zhiwei; Min, Xinping; Li, Bowen; Zhang, Min; Dai, Feifeng; Cai, Xin
Abstract: The surgical therapy of synchronous type A aortic dissection and abdominal aortic aneurysm is complex and rarely reported, especially, when the abdominal aortic aneurysm is unsuitable for intervention. Recently, we have successfully performed sequential two staged surgeries on a 46-year-old woman. The first stage surgeries consisted of the Bentall procedure, total aortic arch replacement, and frozen elephant trunk implantation. The second stage surgeries included replacement from the descending aorta to the sub-renal abdominal aorta, reconstruction of the blood flow to the spinal, the celiac trunk artery, the left and right renal artery, the superior and inferior mesenteric artery, and the iliac artery of both sides. The interval between two surgeries was very short (42 days). The patient was recovered, and all functions of her body were reserved. According to our experience, it is feasible to prevent aortic rupture by short interval staged surgery in selected patients with synchronous type A aortic dissection and un-interventionable abdominal aortic aneurysm. Abstract : Aortic dissection; Abdominal aortic aneurysm; Staged surgery; Medical decision making; Case report.